2012
DOI: 10.4028/www.scientific.net/amr.620.325
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Cell Growth on TiO<sub>2</sub> Nanotubes

Abstract: The in vitro cell response was investigated on flat Ti surface vs nanostructured TiO2 nanotube surface. The titanium dioxide nanotube layers were prepared by electrochemical anodization of Ti in ethylene glycol, 5 wt% NH4F and 1ml H2O2. The nanotube layered structure and morphology were characterized using X-ray diffraction (XRD) and field emission scanning electron microscopy (FESEM). The diameter and the length of the nanotubes are found to increase with anodization voltage. Hs27 and breast cancer cell line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The application of such modification to titanium and its alloys has a positive effect on the bioactivity property of the latter [1]- [3]. This effect has been partly ascribed to the biomimicking of bone nanostructure [4]- [7].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The application of such modification to titanium and its alloys has a positive effect on the bioactivity property of the latter [1]- [3]. This effect has been partly ascribed to the biomimicking of bone nanostructure [4]- [7].…”
Section: Introductionmentioning
confidence: 98%
“…The following decrease was due to the formation of the barrier layer on the titanium alloy sample (Ti whereby i is the current density, E is the electric field across the oxide layer and U is the voltage across the oxide with thickness, d (1). According to equations (1) and (2), as the thickness of the oxide layer d is increased, the current density would decrease exponentially.…”
Section: Anodising Current Variationmentioning
confidence: 99%
“…8,9 TNA have been described previously with unique surface roughness properties, contact angle, and surface energy that is favorable for cell interaction. [10][11][12][13][14][15] Studies have reported that TNA nanosurface provides better cell spreading and differentiation behavior. Most notably, this study has provided insights into understanding the cell-TNA mechanotransduction response.…”
Section: Introductionmentioning
confidence: 99%
“…Successful cell attachment and proliferation on the TNA surfaces suggests that the arrays have good biocompatibility and provide a favourable environment for cell growth, as reported in previous studies. 19 , 20 In addition to NPC cells, HEK 293, a human embryonic kidney cell line, was also observed to confirm the biocompatibility of the TNA nanosystem with both normal and cancer cells ( Figure 2a, b ).…”
Section: Resultsmentioning
confidence: 81%